Witness stress promotes age and sex-dependent behavioral and neurofunctional alterations in the amygdaloid complex and dorsal hippocampus in mice - Avalo-Zuluaga, Julian Humberto [UNESP]; Viatela Ramírez, Stephany [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Canto-de-Souza, Lucas [UNESP]; Rico, Javier Leonardo; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2025)
Humans are frequently exposed to stress, with social stress being a predominant factor, either directly experienced or observed. Chronic stress is linked to psychiatric disorders such as depression and anxiety and induces morpho-functional changes in brain areas like the amygdaloid complex and dorsal hippocampus, which influence emotional responses. This study examined the impact of witness social defeat stress (WSDS) on depression-like behaviors and neural activation in Swiss-Webster mice, considering variables like sex and life stage. Two experiments were conducted: Experiment 1 assessed the effects of WSDS in adulthood (58-60 postnatal days [PND]) on behaviors such as coat state, nest building, novel object exploration, and body weight gain, as well as neuronal activation in the amygdaloid complex and dorsal hippocampus. Experiment 2 evaluated the long-term effects of early WSDS exposure (21 PND) on these same parameters, reassessing mice at 58-62 PND. Results showed sex-dependent behavioral changes, including altered novel object interaction, coat and nest quality, and decreased ΔFosB Protein Expression in the amygdaloid complex and hippocampus, with age and sex influencing the stress response. WSDS in adulthood produced smaller behavioral changes, with some signs of resilience particularly in females, while early exposure to this type of stress led to more pronounced effects. This study highlights the complexity of stress responses, suggesting that the intensity and timing of stress, along with sex, play critical roles in shaping behavioral outcomes.